Viscosity effects on flows of Generalized Oldroyd-B fluids through curved pipes - Pires, Marilia (2020)
Aim of the talk is to study a the effects of viscosity for incompressible generalized Oldroyd-B flows with shear-thinning viscosity flow in curved pipes of arbitrary cross-section and curvature ratio. Flows are driven by a given pressure gradient and behavior of the solutions obtained by the finite element methods, applied to the model written in toroidal coordinates, is discussed with respect to different rheologic and geometric flow parameters.